Modulation of GABA release from the thalamic reticular nucleus by cocaine and caffeine: role of serotonin receptors. Issue 3 (12th November 2015) - Goitia, Belén; Rivero‐Echeto, María Celeste; Weisstaub, Noelia V.; Gingrich, Jay A.; Garcia‐Rill, Edgar; Bisagno, Verónica; Urbano, Francisco J.
Abstract: Serotonin receptors are targets of drug therapies for a variety of neuropsychiatric and neurodegenerative disorders. Cocaine inhibits the re‐uptake of serotonin (5‐HT), dopamine, and noradrenaline, whereas caffeine blocks adenosine receptors and opens ryanodine receptors in the endoplasmic reticulum. We studied how 5‐HT and adenosine affected spontaneous GABAergic transmission from thalamic reticular nucleus. We combined whole‐cell patch clamp recordings of miniature inhibitory post‐synaptic currents (mIPSCs) in ventrobasal thalamic neurons during local ( puff ) application of 5‐HT in wild type (WT) or knockout mice lacking 5‐HT2A receptors (5‐HT2A −/−). Inhibition of mIPSCs frequency by low (10 μM) and high (100 μM) 5‐HT concentrations was observed in ventrobasal neurons from 5‐HT2A −/− mice. In WT mice, only 100 μM 5‐HT significantly reduced mIPSCs frequency. In 5‐HT2A −/− mice, NAN‐190, a specific 5‐HT1A antagonist, prevented the 100 μM 5‐HT inhibition while blocking H‐currents that prolonged inhibition during post‐puff periods. The inhibitory effects of 100 μM 5‐HT were enhanced in cocaine binge‐treated 5‐HT2A −/− mice. Caffeine binge treatment did not affect 5‐HT‐mediated inhibition. Our findings suggest that both 5‐HT1A and 5‐HT2A receptors are present in pre‐synaptic thalamic reticular nucleus terminals. Serotonergic‐mediated inhibition of GABA release could underlie aberrant thalamocortical physiology described after repetitive consumption of cocaine. Our findings suggest that both 5‐HT1A, 5‐HT2A and A1 receptors are present in pre‐synaptic TRN terminals. 5‐HT1A and A1 receptors would down‐regulate adenylate cyclase, whereas 5‐HT1A would also increase the probability of the opening of G‐protein‐activated inwardly rectifying K + channels (GIRK). Sustained opening of GIRK channels would hyperpolarize pre‐synaptic terminals activating H‐currents, resulting in less GABA release. 5‐HT2A ‐would activate PLC and IP3, increasing intracellular [Ca 2+ ] and thus facilitating GABA release. Abstract : Our findings suggest that both 5‐HT1A, 5‐HT2A and A1 receptors are present in pre‐synaptic TRN terminals. 5‐HT1A and A1 receptors would down‐regulate adenylate cyclase, whereas 5‐HT1A would also increase the probability of the opening of G‐protein‐activated inwardly rectifying K + channels (GIRK). Sustained opening of GIRK channels would hyperpolarize pre‐synaptic terminals activating H‐currents, resulting in less GABA release. 5‐HT2A ‐would activate PLC and IP3, increasing intracellular [Ca 2+ ] and thus facilitating GABA release.